The Islamic Institutions in Algeria and the Resistance to Evangelization (1830 – 1914) - Bouabdallah, Abdelhafid (The Algerian Historical Journal, 2026)
Evangelizationis one of the foundations upon which colonialism has been based throughout history. The Crusader tendency was one of the reasons behind the French occupation of Algeria in 1830. The religious dimension of the French military campaign against Algeria is evident from the beginning of the occupation, as well as the various means and methods employed by missionaries, such as Cardinal "Lavigerie" (1864-1892), to achieve the colonial goal of proselytism and to wipe out Islamic institutions